2020
DOI: 10.17576/gema-2020-2004-07
|View full text |Cite
|
Sign up to set email alerts
|

The Interlanguage Pragmatics of Japanese Daily Greetings by Malaysian Learners

Abstract: Scholars in pragmatics argue that the teaching of a second language (L2) must pay extra attention to the language forms and expressions within specific cultural contexts. Not being able to use a L2 according to the nature of its cultural context could sometimes lead to misunderstanding and miscommunication. This study aims to explain the interlanguage pragmatic transfer in daily greetings used by Malaysian learners of Japanese. Using a convenient sampling technique, the respondents are 80 Malay students enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This might be because speakers often tend to look more caring and cordial with the distant interlocutor and use more positive politeness strategies. Furthermore, it is supported by past studies (Al-Qudah, 2001;Bataineh, 2013;Can, 2011;Lodhi & Akash, 2019;Majoko, 2019;Malmir & Derakhshan, 2020;Martín-Laguna, 2020;Meihami & Khanlarzadeh, 2015;Mohd et al, 2020), who found the use of more detailed strategies with interlocutors of distant level and less with close friends and intimates.…”
Section: Finding and Discussionmentioning
confidence: 53%
“…This might be because speakers often tend to look more caring and cordial with the distant interlocutor and use more positive politeness strategies. Furthermore, it is supported by past studies (Al-Qudah, 2001;Bataineh, 2013;Can, 2011;Lodhi & Akash, 2019;Majoko, 2019;Malmir & Derakhshan, 2020;Martín-Laguna, 2020;Meihami & Khanlarzadeh, 2015;Mohd et al, 2020), who found the use of more detailed strategies with interlocutors of distant level and less with close friends and intimates.…”
Section: Finding and Discussionmentioning
confidence: 53%
“…By analyzing cultural texts, the researchers found that Japanese movies frequently relate to high-context communication. Case studies of popular Japanese movies revealed that characters frequently rely on non-verbal cues, shared cultural context, and subtle gestures to convey meaning (Mohd et al, 2020). In the Japanese movie "Lost in Translation", there is a special moment where the lead character, Charlotte, presents a small gift to Bob without explicitly stating its purpose.…”
Section: Example 1: High-context Communication In Japanese Filmsmentioning
confidence: 99%